Utilização de bagaço de malte como biossorvente na remoção, em sistema contínuo, do corante têxtil Direct Blue 251 - Kapp, Marlon Augusto (2018)
The malt bagasse (BM), a residue generated by the breweries, has aroused the interest of researchers in the use as biosorbent, since it is generated in large quantities and presents a low cost. This work aimed to the use of BM as a biosorbent in the removal of the Direct Blue 251 textile dye in aqueous solutions using a continuous system in a fixed bed column. For the adsorption tests, a glass-lined column of 1.2 cm internal diameter and 27 cm length was used. The experiments were performed at a temperature of 30ºC and pH between 5.2 and 5.3. Different masses of the adsorbent (2.0, 2.5 and 3.0 g), different flow rates (1, 2 and 3 mL / min.) And different initial concentrations (29.5 to 109.75 mg / L). From the rupture curves, the factors total time, useful time, rupture time, bed useful height, mass transfer zone and amount of dye adsorbed in BM gram were determined. The results showed that the use of smaller feed rates increases the useful time of the bed, prolonging the operation time of the column and favoring the removal of the dye. The highest amount of dye adsorbed by BM was 22.126 mg / g. Thus, malt bagasse presents itself as an alternative biosorbent with potential to be used in the industry for the treatment of textile effluents.